TAP1 and TAP2 polymorphisms analysis in northwestern Colombian patients with systemic lupus erythematosus. Issue 4 (1st April 2003) - Correa, P A; Molina, J F; Pinto, L F; Arcos-Burgos, M; Herrera, M; Anaya, J-M
Abstract : Objective: To determine the influence of TAP1 and TAP2 alleles in northwestern Colombian patients with systemic lupus erythematosus (SLE). Methods: Unselected patients with SLE (n=140) and controls (n=120) matched for sex, age, and ethnicity were analysed. Clinical manifestations, clinical activity, and severity of disease were recorded. Autoantibodies were detected by enzyme linked immunosorbent assay (ELISA). TAP1 and TAP2 polymorphisms were determined by amplification refractory mutation system-polymerase chain reaction. A Hardy-Weinberg equilibrium test, microdifferentiation analysis, linkage disequilibrium analysis, and haplotype and allele frequency comparisons were performed. Results: The TAP2 variant Val379/Ala565/Ala665 (allele TAP2*0201) was associated with SLE (56% v 39%; odds ratio=2, 95% confidence interval 1.22 to 3.30, pc =0.03). There was no stratification between patient and control samples. Linkage disequilibrium between TAP1 and TAP2 loci was found in controls but not in patients. An excess in the number of heterozygotes in the TAP2 locus was found in patients. No association between TAP1 and TAP2 variants and the presence of autoantibodies, clinical expression, or severity of disease was found. Conclusions: The TAP2 locus influences susceptibility to SLE in our patient group; however, it has no significant effect on the immune response or on the clinical course of the disease.